Experience and expression in the fear of crime, 2003-2004 - Farrall, Stephen (UK Data Service, 2008)
The Experience and Expression in the Fear of Crime, 2003-2004 dataset comprises a secondary data analysis of the main British Crime Survey, 2003-2004 (BCS) (held at the UK Data Archive under SN 5324), and also includes some data taken from a previous survey undertaken by Dr. Jackson. With regard to the BCS data, a particular set of questions on the frequency of the fear of crime was analysed; no new variables were produced as a result, but some new codings of the existing BCS variables are included in this dataset. See documentation for further details. (Note that the main British Crime Survey has now become the Crime Survey for England and Wales, but titles of older studies in the series remain the same.) Further information about the project may be found on the Experience and Expression in the Fear of Crime ESRC award web page. An earlier dataset covering similar topics, Measuring the Fear of Crime with Greater Accuracy, 2002, is also held at the UKDA under SN 4665.